ASP.NET Developer's JumpStart - Sheriff, Paul D. (Addison-Wesley, 2002)
The purpose of ASP.NET JumpStart is to show readers the practical applications of .NET and ASP.NET by illustrating how to build Web-based applications using Web Forms and Web Services. Emphasis will be on good programming standards and practices. The reader will be taken from an introduction of the VB .NET language to intermediate topics through a step-by-step approach, which gives the reader the opportunity to try out the practices presented in each chapter.